Strengthening First Aid Readiness: Formation of the ToS-ReAct To PPFA Task Force for Motorcycle Ride-Hailing Drivers: Penguatan Kesiapsiagaan Pertolongan Pertama: Pembentukan Satgas ToS-ReAct To PPFA untuk Pengemudi Ojek Online - Fitria, Dian; Mustikasari, Mustikasari; S Hamid, Achir Yani; Kimin, Amelia; Chandra, Yudi Ariesta; Adam, Muhammad; Sofyani Kusmara, Irma; Nurfalah, Firhan (Sekolah Tinggi Ilmu Kesehatan RS Husada, 2026)
The high incidence of traffic accidents in urban areas necessitates rapid first-aid responses before professional healthcare providers arrive at the scene. Online motorcycle taxi (ojek online) drivers are community members who are frequently present at accident sites and have the potential to act as first responders; however, they generally lack adequate knowledge and skills in providing physical and psychological first aid. This community service program aimed to strengthen first-aid preparedness through the establishment of the ToS-ReAct To PPFA Task Force (Tolong Sesama – Responsive and Rapid Action for Physical and Psychological First Aid) among online motorcycle taxi drivers in Depok City. The program employed educational and training methods combining theory and practice, covering basic first-aid concepts, Psychological First Aid (PFA) using the 3L approach (Look, Listen, Link), and physical first-aid skills such as cardiopulmonary resuscitation (CPR), simple splinting, and bleeding control. Program evaluation was conducted through pre- and post-tests of knowledge, observation of practical skills, and participant feedback. The results demonstrated an increase in the mean knowledge score from 54 to 72, representing a 42.31% improvement. Furthermore, all participants (100%) were able to correctly demonstrate the components of the PFA 3L approach and physical first-aid skills. This program proved effective in enhancing the capacity of online motorcycle taxi drivers as community first responders and has the potential to strengthen local emergency preparedness systems. Keywords: First aid; Community preparedness; Online motorcycle taxi drivers; Psychological first aid; Cardiopulmonary resuscitation